(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2000)
This area played a key role in defining Middle Triassic stratigraphy. In the nineteenth century the study of several ammonoids collected in the Wengen Formation served as a basis for the definition of the Longobardian substage of the Ladinian. Moreover, during the 1960’s the modern Triassic Lithostratigraphy of Lombardy was founded on sections from this area. The present study represents the first bed-by-bed sampling of this area and is focused mainly on the Wengen Formation and Pratotondo Limestone. In particular, conodonts were found in both units for the first time. The age of some Middle Triassic formations is revised: the top of the Wengen Formation belongs definitively to the Lower Carnian in a sizeable portion of the study area. The overlying carbonate platform, previously attributed to the Upper Ladinian Esino Limestone, is instead Carnian and is coeval to the Breno Formation in the Southern Camonica Valley. the Pratotondo Limestone is dated Late Ladinian/Early Carnian, while the overlying Lozio shale is Carnian. These new data contradict the equivalence "Wengener Schichten" = Archelaus Zone = Longobardian so common in the literature. We demonstrate that the Regoledanus Zone represents a great part of the Wengen Formation. Moreover, at the top of the Wengen Formation the ammonoid and conodont fauna represents the early Carnian Daxatina or Aon Zone. The biochronostratigraphic revision of the basinal formations requires modification of both the chronostratigraphic schemes and the paleogeographic history of the lombardian Southern Alps during Ladinian-Carnian time.